Uganda : An Indian Colony, 1897-1972 - Lunyiigo, Samwiri Lwanga (Uganda : The African Studies Bookstore, 2021)
The long and short of this book is that it puts the spotlight on Indians in east Africa narrating them as deputy imperialists, sub-imperialists, privileged workers of the colonialists. The core argument is that the dominant status Indians came to enjoy in Uganda's economy (and East Africa more generally) was only possible because the British colonialists - those who had brought them privileged them, and practically and violently crushed local investors and their initiatives. The Indians on their part, embraced their privileged positions, and with a touch of racism, exploited Natives in ways that sometimes shocked the British - especially newer administrators from London. With impeccable reading of the archive, this book shows that before Indians/Asians were expelled from all East Africa (1965-1972), Natives in this region had received no independence. In fact as Mamdani(1995) put it, only the Indians had received independence from the British in the 1960s. With the British departure, Indians/Asians now dominated East Africa's economy with no restriction, profiting both for themselves, and their benefactors now confined to London.